High temperature superconducting flux pump : a thesis in the partial fulfilment of the requirements for the degree of Masters of Engineering in Mechatronics at Massey University, Turitea Campus, Palmerston North, New Zealand - Walsh, Rowan Martin (Massey University, 2011)
Electromagnets play an important role in everyday life from motors and generators to such devices as Magnetic Resonance Imaging (MRI). The larger a magnetic field needed in such a device the more demand there is in power consumption and space. The development of superconductors (SC) and their ability to dissipate negligible power has made it possible to create larger fields in a more cost effective and space efficient manner. The disadvantage of the SC is that it needs to be operated at cryogenic temperatures (typically below 110 K). Cryogenics is a significant cost factor so the less power needed for cooling a SC magnet the more cost effective the system can become. The main heat load comes from the ohmic dissipation of the current leads necessary to energise the magnet. The current leads provide the electrical connection from the power supply at room temperature to the coils in the cryogenic environment. To circumnavigate this heat load a superconducting device known as a flux pump (FP) can be embedded in the cryogenic environment. The flux pump operation can be generalised as a DC generator, which minimises ohmic heating and makes the power supply needed to energise the magnet superfluous. HTS 110 is a magnet manufacturer who has assigned the task of implementing a flux pump into a commercial magnet application and developing a complete system capable of controlling a homogenous current level in their magnets. Such a flux pump module was developed and successfully incorporated into an existing SC magnet. This thesis details the mechanical design, control hardware, required software used to create this technology and the benefits it presents. Compared to the current lead technology, the developed flux pump module reduced the heat load on the cryo-cooler by almost a factor of 5. In addition a produced magnetic field of 750 mT was achieved, which corresponds to a current of 68 A in the magnet coils. Such a high field could not have been obtained in the present setup with conventional technology. The large heat load caused by current leads would increase the overall temperature of the coils and in turn decrease the current capability of the circuit to approximately 20 A, resulting in a field that is more than three times smaller. A full control system using field strength as feedback to control the rotation of the FP was implemented. This included an iterative hardware design and fabrication process followed by software implementation, that led to a high level system encompassing a PID type control algorithm. The control system achieved a field stability of 30 parts per million (PPM) which puts the system in reach for the needed NMR stability criterion of 1 PPM.
Keywords: Superconducting magnets; Heat load; Flux pump; Electromagnets